Environmental and Financial Management in Sustainable Business: A Case Study in the Energy Industry - Muhammad Nur Afiat; Anita Lestari; Syamsu Rijal; Ari Purwanti; Nurul Afifah (The Eastasouth Management and Business, 2023)
Sustainable business practices have become paramount in the contemporary global economy, urging companies to balance financial prosperity with environmental responsibility. In this context, the energy industry in West Java, Indonesia, serves as a compelling case study due to its significance in the region's economic development and its simultaneous environmental challenges. This research employs a qualitative case study approach to investigate the complex interplay between environmental and financial management within the West Java energy sector. Through semi-structured interviews, document analysis, and surveys, the study assesses environmental management practices, financial performance, and sustainable business models. The findings reveal a growing commitment to clean technologies, emissions reduction, and transparency among energy companies. Moreover, sustainable energy businesses exhibit competitive profitability, risk mitigation capabilities, and improved access to capital. Successful business models emphasize the integration of environmental and financial objectives and the importance of stakeholder engagement. These findings underscore the significance of aligning environmental and financial management for sustainable business in the energy industry and offer valuable insights for policymakers and industry practitioners seeking to navigate the intricate terrain of sustainability.